PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 018 RAMBA SAMO - Bakri, Juwita; Elvina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of implementing the Problem-Based Learning (PBL) model in improving the mathematics learning outcomes of fifth-grade students at SD Negeri 018 Rambah Samo. The background of this research lies in the low academic achievement of students in mathematics, often caused by conventional teaching methods that do not actively engage students in the learning process. The PBL model was chosen because it encourages critical thinking, problem-solving skills, and increases student engagement in learning activities. This research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 9 fifth-grade students. Data were collected through observation, learning outcome tests, and documentation. The results showed an increase in the students’ average scores from 61.33 before the intervention to 72.2 in the first cycle, and further to 80.9 in the second cycle. Additionally, student participation and enthusiasm in learning activities also showed significant improvement.